The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/01605682.2021.1979902
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the causal impact of an intervention on efficiency in a dynamic setting

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…The higher the value, the poorer the school infrastructures. The inclusion of the socioeconomic background of the students as an environmental variable is in line with previous literature (see Mergoni and De Witte, 2021b). The moderating effect of such environmental variables has been investigated in previous research, which demonstrated the relevance of their integration in efficiency models (De Witte & Kortelainen, 2013).…”
Section: Datasupporting
confidence: 67%
“…The higher the value, the poorer the school infrastructures. The inclusion of the socioeconomic background of the students as an environmental variable is in line with previous literature (see Mergoni and De Witte, 2021b). The moderating effect of such environmental variables has been investigated in previous research, which demonstrated the relevance of their integration in efficiency models (De Witte & Kortelainen, 2013).…”
Section: Datasupporting
confidence: 67%